On the banks of Plum Creek - Wilder, Laura Ingalls, 1867-1957 (Wilder, Laura Ingalls, 1867-1957. Little house books., 1953)
Laura and her family move to Minnesota where they live in a dugout until a new house is built and face misfortunes caused by flood, blizzard, and grasshoppers.